THE EXPRESSION OF COLLECTIVE ASSOCIATION IN THE SPEECH OF CHILDREN UP TO SCHOOL AGE (ON THE EXAMPLE OF LEXICAL ASSOCIATIONS IN ANTI-SEMITIC AND ENANTIOSEMIC CONTEXTS) - Mirnosirova Dilbar Nodirbek kizi (European Journal of Interdisciplinary Research and Development, 2023)
The article provides an analysis of collective associations of antisemitic and enantiosemic attitudes observed in the speech of preschool children, which uses such types of linguistic research methods as description, classification, and component analysis.